Profit and Loss Sharing (PLS) and Non-PLS Financing in Malaysia: Which One Should Be the One? - Mohd Nor , Amirudin; Ismail, Shafinar (KnE Social Sciences, 2020)
The motivation in this study lies on the fact that despite the tremendous development of the Islamic finance industry, some scholars argue that the development was driven by the debt-based or non- Profit sharing and losses sharing (PLS) contract instead of the widely proposed Profit sharing and losses sharing (PLS) contracts perceived to be as the ideal mode of financing. The question that arises is why non-PLS based? Why not PLS? Which one should the concepts use in Islamic finance then? Hence, this paper tries to explore the reason behind such development, discuss the future development as well and finally answer the main issue of which one should be the one? Initially the PLS was introduced in Malaysia; however the trend moved to non-PLS as a result of the current situation. The introduction of non-PLS products has been approved by shariah scholars hence making it shariah compliant. Since ‘sin’ is not an issue anymore, the investors now look for the best instrument that can give them higher return in line with the investment concept of high risk high return. Therefore, both PLS and non-PLS can be used side by side at the present moment. Keywords: Profit and loss sharing; Islamic finance concept; Malaysia